Answer:
You can divide both sides of the equation by
.
Explanation:
When you divide both sides of the given equation by
, well end up with the equation,
.
Solution of dividing both sides of the equation by
:
![3(x -7) = 15 \\ (3(x -7))/(3) = (15)/(3) \\ x -7 = 5](https://img.qammunity.org/2022/formulas/mathematics/high-school/65jzvgjmhnl8wb6rqohcf67iu5j6gf6ob6.png)
You can then add
to the both sides of the equation, you'll then find your solution of the equation which is
.
Solution of adding both sides of the equation by
:
![x -7 = 5 \\ x -7 +7 = 5 +7 \\ x = 12](https://img.qammunity.org/2022/formulas/mathematics/high-school/rpeuxxo4lw5us3z1f0mycaqlju4sl0qmlo.png)